2013
DOI: 10.3109/02703181.2013.854858
|View full text |Cite
|
Sign up to set email alerts
|

Thinking and Acting in a New Way: Influences of a Falls-Prevention Program on Participants' Everyday Life

Abstract: In Sweden, a new type of program called "Active lifestyle all your life" has been developed in primary care. It is a multidisciplinary program aimed at the decrease of accidental falls and at promotion of the health benefits of staying engaged in valued occupations. As one part of the evaluation of this program, this study aimed to explore and understand if, and how, participating in the program influenced each individual's everyday life narratives. Data was collected using a narrative approach with repeated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…Meanwhile, in studies related to this program (Johansson, Borell, & Jonsson, 2014; Johansson & Jonsson, 2013) the findings support the view that the program had some impact on the participants’ everyday occupations, but the impact was described in other terms than participation. The participants spoke not only of processes of change such as new strategies of thinking but also of doing occupations in another way.…”
Section: Discussionsupporting
confidence: 60%
“…Meanwhile, in studies related to this program (Johansson, Borell, & Jonsson, 2014; Johansson & Jonsson, 2013) the findings support the view that the program had some impact on the participants’ everyday occupations, but the impact was described in other terms than participation. The participants spoke not only of processes of change such as new strategies of thinking but also of doing occupations in another way.…”
Section: Discussionsupporting
confidence: 60%
“…Enfin, en ce qui concerne la satisfaction des participants, la faisabilité et l’acceptabilité du programme, l’attitude positive et l’approche des animateurs soulevées par l’ensemble des participants de Marche vers le futur sont similaires aux commentaires recueillis lors de l‘évaluation du programme Equilibreizh (Faure, 2012). De même, le degré de satisfaction globale des participants envers le programme est semblable à celui d’autres programmes de prévention des chutes (Faure, 2012 ; Johansson et Jonsson, 2013) et le taux d’assiduité est légèrement supérieur à celui observé pour le programme PIED (Filiatrault et al, 2007). Ces résultats soutiennent l’acceptabilité de la vidéoconférence comme moyen d’améliorer les capacités physiques des personnes âgées vivant en régions éloignées ou en contexte linguistique minoritaire.…”
Section: Discussionunclassified
“…In relation to five of the original studies, eight related studies explored the experiences of participants [75,76,82,85] or both the experiences of participants and professionals delivering the intervention [61,62,87,91]. Based on qualitative methods and interviews, participants' experiences were described related to i) a single preventive home visit (PHV) [75], ii) senior meetings [76,82,85,87], iii) multidisciplinary fall prevention programmes [61,62], and iv) case management intervention [91].…”
Section: Participants' Experiencesmentioning
confidence: 99%
“…The involved professionals observed that building trust and a safe atmosphere within the group increased participants' engagement in discussions which contributed to the success of the intervention. A contributing factor for creating this sort of atmosphere was the role-shifting negotiated by the group leaders from being the expert to being a facilitator of the discussion [61,62]. However, it was noticed that for a group format to be successful, group composition should be taken into consideration for the participants to feel fellowship [61,82].…”
Section: Participants' Experiencesmentioning
confidence: 99%
See 1 more Smart Citation